Improving the Effectiveness of the Music Culture Lesson use Modern Information Technologies Significance - Rustamjonova Dilkhavas Ravshvnbek kizi (Research Parks Publishing LLC, 2023)
Information technology is the process of using complex methods and means of collecting, processing, and transmitting information to qualitatively display new information from one perspective to another. This article discusses the specificity and importance of using modern information technology to organize classes in order to increase the effectiveness of music culture classes.